Game Learning Model Through Developmentally Appropriate Practice (DAP) Approach to Increase Elementary School Students' Learning Motivation - Mufakkirul Ardi; Nurlan Kusmaedi; Tite Juliantine; Dian Budiana (Jurnal Pendidikan dan Pengajaran, 2025)
Teachers' knowledge of learning strategies that refer to the objectives of an activity is less varied, resulting in low student learning motivation. This study aims to develop an android-based game learning model for elementary school students through the Developmentally Appropriate Practice (DAP) approach. This study is a type of development research (R&D) using the ADDIE development model. Data collection techniques in this study are quantitative data through material validation questionnaires, learning design validation, learning media validation, and determination of validation classification by experts based on the number of answer scores. Data are analyzed and processed descriptively into interval data using a Likert scale. The results obtained are in the form of an android-based game learning model flow through the Developmentally Appropriate Practice (DAP) approach, which is compiled through an android application as a guideline for elementary school PJOK teachers to use this model in elementary school PJOK learning, the results of the feasibility assessment based on material validation with a score of 62 or 88.57%, a learning design validation score of 52 or 86.67%, and a learning media validation score of 69 or 92%. As well as the teacher's assessment as a practitioner of 91.02%. The effectiveness test results showed differences in student learning motivation before and after the implementation of the Android-based game learning model through DAP. It was concluded that the game learning model that had been developed was declared effective for use in PJOK learning of game material in Elementary Schools.